Nilai-Nilai Pendidikan Bagi Manusia Dalam Hukum Islam - Syhabudin, Abu; Ayu Gumilang Lestari; Dedi (Al-Mau'izhoh: Jurnal Pendidikan Agama Islam, 2023)
This study aims to determine the values of education for humans contained in Islamic law. The research method uses library research through a book survey, namely the study of books/books of Tafsir, Fiqh and books on education. Data analysis uses content analysis, namely data analysis on Islamic law material that is studied about education. Through the study of Tafsir al-Qur'an, Hadith syarah and opinions of Ulama in Fiqh Science. The results of the study found that Islamic law in fact has high educational values. Islamic law provides a number of rules that humans must follow. The rules contain the rules governing human relations with God and humans with humans. All of that leads to benefit for the human self and the natural surroundings. Allah's rules which are contained in Islamic Law, in principle, are to educate people to have good morals and bring benefit to all.